Encyclopedia of Information Science and Technology, Fourth Edition 2018
DOI: 10.4018/978-1-5225-2255-3.ch194
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy for the 21st Century

Abstract: Before the Internet was an integral part of life, Paul Gilster (1997) defined digital literacy as the “ability to understand and use information in multiple formats from a wide range of sources when it is presented via computers” (p. 1). Thus, digital literacy involves any number of digital reading and writing techniques across multiple media forms. These media include words, texts, visual displays, motion graphics, audio, video, and multimodal forms. There are myriad cognitive processes at play, along a conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 14 publications
0
19
0
5
Order By: Relevance
“…Two of the skills probed, namely, “computer literacy” and “information retrieval,” can be clustered and expanded to form “digital technical skills” and the broader concept of “digital literacy,” which were not probed in this survey. Digital technical skills and digital literacy are proposed to become increasingly critical to employability in the future (Spires, Paul, & Kerkhoff, 2018), and are also essential for life‐long learning (Coetzee, 2014), an aspect of graduateness. As such, they were identified as requirements for food science and technology graduates and a potential area for improvement within existing South African food science and technology programs.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the skills probed, namely, “computer literacy” and “information retrieval,” can be clustered and expanded to form “digital technical skills” and the broader concept of “digital literacy,” which were not probed in this survey. Digital technical skills and digital literacy are proposed to become increasingly critical to employability in the future (Spires, Paul, & Kerkhoff, 2018), and are also essential for life‐long learning (Coetzee, 2014), an aspect of graduateness. As such, they were identified as requirements for food science and technology graduates and a potential area for improvement within existing South African food science and technology programs.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, scholars have advanced several DL frameworks. For instance, Spires and Bartlett (2012 as cited by Spires et al, 2018) identified the building blocks of digital literacy: (a) locating and consuming digital content, (b) creating digital content, and (c) communicating digital content. Moreover, a digitally-literate person is able to search and understand desired information, express and share opinions freely, and have a better understanding of others (Kwon and Hyun, 2014).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Digital literacy is the ability to use information and communication technologies to find, evaluate, create and communicate information, requiring both cognitive and technical skills [1]. Huller Spires of North Carolina State University views digital literacy in the three buckets:  Finding and consuming digital content  Creating digital content  Communicating or sharing [2] India's National Digital Literacy Mission trains people to operate digital devices and to access the government's egovernance services at its basic levels.…”
Section: Introductionmentioning
confidence: 99%